Fe(III)-Catalyzed diastereoselective friedel-crafts alkylation-hemiketalization-lactonization cascade for the synthesis of polycyclic bridged 2-chromanol lactones - Borade, Balasaheb R.; Nomula, Rajesh; Gonnade, Rajesh G.; Kontham, Ravindar (Organic Letters, 2019)
An unprecedented Fe(III)-catalyzed Friedel-rafts alkylation-hemiketalization-lactonization cascade of electron-rich hydroxy arenes and distinctively functionalized unsaturated 4-keto esters is developed for the construction of polycyclic bridged 2-chromanol lactones. Following this simple and facile protocol, a broad range of products was prepared in good to excellent yields as a single diastereomer. An unusual conglomerate (enantiomerically pure polymorph) of 3ac is reported along with the absolute stereochemistry, and the remaining products were rigorously confirmed by single-crystal X-ray analysis and analogy.

Studies directed toward the synthesis of hedycoropyrans: total synthesis of des-hydroxy (-)-hedycoropyran B (ent-rhoiptelol B) - Kataria, Priyanka; Nomula, Rajesh; Kontham, Ravindar (Organic & Biomolecular Chemistry, 2022)
A full account of our efforts directed towards the synthesis of the diarylheptanoid-derived natural products hedycoropyrans that led to the total synthesis of ent-rhoiptelol B is described. In this endeavor, we have attempted two distinct synthetic strategies to access hedycoropyrans A and B, which led us to establish a facile synthetic route for des-hydroxy (-)-hedycoropyran B (ent-rhoiptelol B) from simple and readily accessible building blocks of 4-allylanisole and vanillin, employing Sharpless asymmetric epoxidation, CBS reduction, and an intramolecular AgOTf-catalyzed oxa-Michael reaction of suitably functionalized hydroxy-ynone as key transformations. The investigations disclosed herein will provide insights into designing novel synthetic routes for THP-DAH-derived natural products.

Studies directed toward the total synthesis of nannocystin A - Nomula, Rajesh; Pratapure, Madhukar S.; Kontham, Ravindar (ChemistrySelect, 2022)
A full account of our efforts directed toward the stereoselective total synthesis of nannocystin A, a macrocyclic myxobacterial metabolite, is presented. In this endeavor, we have attempted two distinct synthetic routes to access polyketide fragment (C1-C11) of macrocyclic depsipeptide (21-membered) natural product from readily accessible building blocks 1,3-propanediol and benzaldehyde employing Evans aldol, CBS reduction, Heck cross-coupling, and Sharpless asymmetric epoxidation as key transformations. Ultimately, accomplished the synthesis of the complete skeleton (21-membered precursor for macrocyclic depsipeptide) of the nannocystin A possessing desired stereochemistry and functional groups.
Keywords: amidation; Depsipeptide; Evans aldol reaction; Macrocycle; Nannocystins